SOCIALIZATION OF YOUTH AS A FACTOR IN THE DEVELOPMENT OF SOCIETY - Tursunov Mukhiddin Boltaevich (American Journals, 2024)
This scientific article reveals the problems of the role of youth socialization in the development of society. This is characterized by the fact that this phenomenon is extremely complex, diverse, contradictory and is considered in different semantic planes and from the point of view of different approaches. The relevance of the topic under study requires clarification, development and resolution of the problem of socialization of youth in modern conditions, as well as substantiation of the model of a viable personality type of a young person.
Keywords: Society, youth, socialization, values, upbringing, traditions, education.